Bilingual Education In Indonesia: Between Idealism and the Reality - Dwi Jayanti; Anton Sujarwo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Today English plays an important role in the development of education. In response to advances and develops the education in this globalization era, English bridges communication among people around the world. The ability to communicate in English becomes crucial. The development in education as an impact of globalization significantly influence the process of teaching and learning concept. Bilingual education becomes necessary, it can stimulate the cognitive ability especially on cognitive function, it can also motivate the bilingual program. Education as a conscious effort to build and develop the quality of human resources and one popular education system promote bilingual education becomes a choice by parents. Using bilingual education become popular and be needed. Indonesian educational policies see this phenomenon as a new modern solution to be practiced in Indonesia's education system for many years. For these reasons, the purpose of writing this library research article paper is to elaborate and give understanding about bilingual eduacation in Indonesia for certain time. The article start with the differences between bilingual and bilingualism, the relation of the bilingual process with executive function, the practice of bilingual education in Indonesia compared by the national standardized school, the challenges and solutions concerning the policy and practices in language teaching and learningÂ focused on bilingual education in Indonesia. The present article employ a descriptive qualitative approach from reputable references which is relevant to the topics.